IMPROVING THE CHARACTERISTICS OF PNEUMATIC TRANSPORT OF GRAIN - Mošorinski, Predrag; Prvulovic, Slavica; Palinkaš, Ivan (Journal of Applied Engineering Science, 2017)
Pneumatic transport is the most commonly performed transport of fine-grained and powder materials to manufacturing plants. It is believed that in this way there is the most economical transport within the production company for processing granular and powdered materials. The need for this kind of transport more sustainable, improve and perfect encouraged the authors of this paper to address this issue. It is assumed that at a certain point transport system choked due to unforeseen circumstances so it is necessary to make urgent additional works to be returned to the operating mode of the system.Tendency is to make the system predictable and downtime to a minimum.
Keywords: Pneumatic transport; Granular materials; Oilseeds; Damaged grains; Pipe system